Electrodeposition of lead at boron-doped diamond film electrodes: Effect of temperature - Prado, C; Wilkins, S; Grundler, P; Marken, F; Compton, R (2003)
The electrodeposition of lead on boron-doped diamond has been studied with a view to identifying the fundamental parameters controlling the sensitivity and lower detection limit in anodic stripping voltammetry. Chronoamperometric transients are used to explore the deposition, indicating a progressive growth mechanism confirmed by ex situ AFM images. Linear sweep ASV experiments show a threshold concentration of ca 10-6 M below which no lead is detected; this is attributed to the need for nucleation of the solid phase on the electrode. Experiments with variable temperature show that this threshold can be usefully lowered at elevated temperatures.